Morpho-phylogenetic analyses of two novel edible mushrooms from China and a mini review of Lyophyllum (Agaricales, Lyophyllaceae) cultivation and bioactivities - Song-Ming Tang; Feng-Ming Yu; Samantha C. Karunarathna; Zong-Long Luo; Kai-Yang Niu; Rui-Yu Li; Lin Li; Xi-Jun Su; Shu-Hong Li (MycoKeys)
Lyophyllum plays an important role in the natural ecosystem and has significant economic value. Some species of this genus have been cultivated in Asia, America, and Europe. This study describes four edible species of Lyophyllum, two of which were newly discovered. Lyophyllum edulis has a dark grayish orange pileus, a grayish orange upper part of the stipe, and globose, subglobose to broadly ellipsoid basidiospores, while L. sinense has a dark gray-orange when injured pileus, dark grayish orange points and lines on the stipe surface, and quadrangular to broadly fusiform basidiospores. Molecular phylogenetic analyses using the internal transcribed spacer ITS1-5.8S-ITS2 ribosomal RNA (ITS), the large subunit ribosomal RNA (LSU), the second-largest subunit of RNA polymerase II (rpb2), and translation elongation factor 1-alpha (tef1-α) indicated that L. edulis is related to L. shimeji, L. heimogu, and L. decastes, and L. sinense has an affinity to L. bulborhizum and L. nigrum. We also summarize the cultivation techniques of the two edible species, L. shimeji and L. decastes.